Quantity and Quality of Oestrus of Kacang Goats Injected with Prostaglandin F2alpha in the Vulva Submucosa on the Coast of Tomini Bay - Ilham, Fahrul; Panggulu, Zulkifli; Dako, Safriyanto; Fathan, Suparmin; Rachman, Agus Bahar (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2025)
Tomini Bay is the longest bay in Indonesia which is located in the provinces of North Sulawesi, Gorontalo and Central Sulawesi. The dominant goat species raised by farmers in Tomini Bay is the Kacang goat. This research aims to determine the quantity and quality of estrus of peanut goats based on different parities that are reared traditionally in Tomini Bay. The hormone used is the PGF2Î± lutalyse brand, which is injected into the vulvar submucosa in 1 ml. The research location is Bonepantai District, Bone Bolango Regency, Gorontalo Province. The number of selected female goats used was 9 goat, and they were grouped into 3: the heifer treatment group, the group that gave birth once, and the group that gave birth more than once. The oestrus quantity variables observed were percentage of oestrus, onset of oestrus, and duration of oestrus. The results of the study showed that administration of the PGF2Î± hormone in the vulva submucosa of kacang goats during the second injection was able to cause up to 100% lust symptoms. The onset and duration of oestrus in heifers injected with PGF2Î± was 57.67 hours for 39.33 hours, one birth was 61.33 hours for 34 hours, and one birth was 57.67 hours for 42.33 hours. The behavior shown by Kacang goats after PGF2Î± injection is that they like to mount their friends and are quiet when mounted by males. The conclusion of this study is that PGF2âˆ injection into the vulva submucosa causes Kacang goats to be in heat with quite obvious symptoms. PGF2âˆ injection into the submucosa vulva can be applied during estrus synchronization at a lower cost but is able to provide a normal heat effect.